Konstruktivisme Lev Semonovich Vygotsky dan Jerome Bruner: Model Pembelajaran Aktif dalam Pengembangan Kemampuan Kognitif Anak - Tohari, Begjo; Rahman, Ainur (Lembaga Sosial Rumah Indonesia, 2024)
Purpose – The constructivist learning theories of Vygotsky and Bruner highlight the effectiveness of learning through interaction, collaboration, and cognitive apprenticeship. Both theorists design instructional strategies that prioritize students' cognitive development, fostering creativity, deep understanding, and meaningful learning. While contributing significantly to education, the application of constructivism has its advantages and disadvantages. This research will discuss the principles and concepts of constructivism according to Vygotsky and Bruner, as well as analyze its strengths and weaknesses in classroom learning.Methods – This research employs the literature review method, commonly known as a literature study. In this literature review, the researcher will analyze theories related to the existing materials. The data analysis technique used is thematic analysis, examining key ideas and organizing them into themes and the focus of the research.Findings – The results of this research found two important concepts in Vygotsky's theory, namely the Zone of Proximal Development (ZPD) and scaffolding. Then the discovery learning theory discovered by Bruner is understanding concepts, meanings, and relationships through an intuitive process to finally arrive at a conclusion called discovery learning. Bruner considers that discovery learning corresponds to the active search for knowledge by the learner and provides the best results. Trying to find solutions to problems produces knowledge that is truly meaningful as learning, especially for students. Research Implications – The results of this study show that implementing constructivism requires sufficient time and resources while evaluating student progress can be a difficult task. There have also been criticisms of the ZPD concept that it may have limitations in encompassing the individual diversity of students. In implementation, some teachers may experience difficulties in adopting constructivist principles without adequate training or support.